2014
DOI: 10.1002/2014jc010173
|View full text |Cite
|
Sign up to set email alerts
|

Quad‐polarization SAR features of ocean currents

Abstract: A methodology is demonstrated to exploit the polarization sensitivity of high-resolution radar measurements to interpret and quantify upper ocean dynamics. This study particularly illustrates the potential of quad-polarization synthetic aperture radar (SAR) measurements. The analysis relies on essential characteristics of the electromagnetic scattering mechanisms and hydrodynamical principles. As the relaxation scale of centimeter-scale ocean surface scatters is typically small, radar signal anomalies associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
83
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 44 publications
6
83
1
1
Order By: Relevance
“…Kudryavtsev et al [5] indicated that the ocean surface current signatures are mostly dominated by non-Bragg backscatter through the analysis of the VV and HH polarizations from quad-polarized RADARSAT-2 SAR images. However, in this study, we remove the non-Bragg backscatter before extracting the current features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kudryavtsev et al [5] indicated that the ocean surface current signatures are mostly dominated by non-Bragg backscatter through the analysis of the VV and HH polarizations from quad-polarized RADARSAT-2 SAR images. However, in this study, we remove the non-Bragg backscatter before extracting the current features.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, spaceborne active microwave synthetic aperture radars (SARs) have been reported as a potential tool for the detection of sea surface currents [5]. SAR techniques can be grouped into two on October 22 are the composite data acquired for a period extending over five days.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism of scattering from the wave-breaking zones and, accordingly, the issue of the scatterer velocity in them have not been fully clarified, much attention is paid to the development of the corresponding scattering models in [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…There exists no consensus in the body of capillary wave spectral data that suggests a clear expected behavior. Observational spectra [6,9] that extend into the capillary or near-capillary regime are sparse, while empirical/parameterized spectra [13,15] vary greatly in that domain, owing largely to the diverse range of observations and theoretical frameworks invoked in their construction [1,13,15]. …”
Section: Discussionmentioning
confidence: 99%
“…These techniques rely on back-scattering of transmitted radar signals by short ocean waves. Scattering models [1] depend upon the short ocean wave spectrum (i.e., decimeters and smaller -the range for which capillary effects become significant) in the determination of the normalized radar cross section (NRCS), or σ  -a quantity of primary importance for the retrieval of meteorological and oceanographic parameters from satellite images. The ability to accurately collect these parameters remotely is a powerful one -sea surface waves are of crucial significance to all manner of interactions between the atmosphere and ocean.…”
Section: Introductionmentioning
confidence: 99%